The Transformation of the ‘modern’ axis of nineteenth-century Istanbul: property, investments and elites from Taksim Square to Sirkeci Station - Tanatar-Baruh, Lorans. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2009., 2009)
The “construction” of the “modern” axis of nineteenth-century Istanbul is analyzed through its three complementary facets: laws and regulations brought on property ownership including everyday practices; investments in “new” commercial buildings and apartment blocks at the core of the city; and the capitalist elite, who by taking advantage of the Tanzîmât reforms, which protected people from arbitrary interference in their private and commercial dealings, invested in these buildings. The dissertation tries to investigate, at a micro level, to what extent Istanbul’s urban fabric may have been the product of capitalism and of its elite consisting of both Ottoman bureaucrats and of the business elite as precursors of the modernization process, and sheds light on the power game between different agencies involved in the process. Such an analysis could only be possible through a multiplicity of perspectives and approaches. In an interdisciplinary fashion, political, economic, social, urban and institutional history is used in combination to trace the background of the transformation of the urban fabric. A quantitative approach is also applied to analyze the “modern” building stock, to follow its evaluation through time, define its peculiarities and trace its topography. This method also helps us to quantify the size of investments and to identify the family names which constitute our sample. To know more about the background of these families a prosopographic approach is also followed. This research is largely based on the sources of the Ottoman State Archive; on sources in private archives, such as the Ottoman Bank Archive and Research Centre, Saint Peter Church or Nissim de Camondo Museum archives; and printed sources such as insurance maps and trade directories.
Keywords: City planning -- Istanbul (Turkey) -- History -- 19th century.